BRINGING THE HISTORY OF MUSIC TO THE STAGE: THE INFLUENCE OF TRADITIONAL AND CONTEMPORARY WORKS ON STUDENTS' WORLDVIEW - Abdurayimov Faxriddin Muxammadali o‘g‘li (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Annotation: This article explores how presenting music history through staged performances can deepen students' understanding and appreciation of both traditional and contemporary compositions. It highlights the educational value of combining historical context with live artistic expression and examines how such experiences shape the intellectual, emotional, and cultural worldview of young learners. By integrating performance with theory, schools can create more immersive and meaningful music education environments that bridge the past and present, fostering critical thinking, creativity, and cultural identity.